PENGARUH BUDAYA ORGANISASI DAN EMPLOYEE ENGAGEMENT TERHADAP KINERJA KARYAWAN PADA PT BANK PEMBANGUNAN DAERAH LAMPUNG - Sindiantika, Nafa Indah; Bakti, Dadang Karya; Adistya, Diang (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2024)
The culture of an organisation plays an important role because a good culture will provide comfort which then supports theperformance of its members. PT Bank Lampung is part of theLampung Regional Development Bank, which naturally has a unique organisational environment and work culture. This studyaims to determine the effect of organisational culture (X1),performance engagement (X2) on employee performance (Y). Thisresearch uses a quantitative approach with the type of explanatoryresearch, the research sample totalled 69 respondents who are employees of PT Bank Lampung. The presentation of the research results explains that organisational culture, good performance attachment will affect employee performance in an organisation, especially at Lampung Regional Development Bank. From theregression analysis, it is found that organisational culture andperformance attachment together have a simultaneous and partialinfluence on employee performance. This shows thatorganisational culture and performance attachment play animportant role in improving employee performance together partially and simultaneously. organisational culture and performance attachment are two important factors in improvingemployee performance. Organisations should create a goodorganisational culture and expand training and development to improve performance attachment in the team.